2014
DOI: 10.4238/2014.april.14.7
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters for total milk yield over multiple ages in Brazilian Murrah buffaloes using different models

Abstract: ABSTRACT. The objective of this study was to estimate variance components and genetic parameters for accumulated 305-day milk yield (MY305) over multiple ages, from 24 to 120 months of age, applying random regression (RRM), repeatability (REP) and multi-trait (MT) models. A total of 4472 lactation records from 1882 buffaloes of the Murrah breed were utilized. The contemporary group (herd-yearcalving season) and number of milkings (two levels) were considered as fixed effects in all models. For REP and RRM, add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Random regression has been used in most studies to model the additive and permanent environmental effects with homogenous or heterogeneous residual effect [ 1 ]. RRM allows changes in variance along the trajectory and provides the accurate estimation of breeding value compare to repeatability and multiple trait models [ 2 ]. The Mean trend of milk yield or 305-day total yield can be modeled with different orders of orthogonal Legendre polynomial because Legendre polynomial produces the lower correlation between parameters than other functions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Random regression has been used in most studies to model the additive and permanent environmental effects with homogenous or heterogeneous residual effect [ 1 ]. RRM allows changes in variance along the trajectory and provides the accurate estimation of breeding value compare to repeatability and multiple trait models [ 2 ]. The Mean trend of milk yield or 305-day total yield can be modeled with different orders of orthogonal Legendre polynomial because Legendre polynomial produces the lower correlation between parameters than other functions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, the genetic analyses for milk yield of buffalo are carried out using a finite dimensional model, as described in other studies (Rosati & Van Vleck, 2002). However, worldwide, RRM are currently being used for national genetic evaluations of dairy cattle in several countries, such as the United States, Canada, Australia, and Brazil (Sesana et al, 2014). Therefore, it is crucial to apply these models in a genetic evaluation program for milking buffalo in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…These values can be considered high, indicating that this trait was influenced by genetic factors and therefore should respond well to selection. In the literature values ranging from 0.14 to 0.29 were observed (Tonhati et al, 2004;Ghaffar et al, 2007;Malhado et al, 2009;Rodrigues et al, 2010;Bezerra Jr. et al, 2014;Sesana et al, 2014), being of medium magnitude. In other studies, Campos et al (2007) found a heritability of 0.26 for cumulative production on 305 days of lactation using dairy buffaloes in 13 farms in São Paulo State.…”
Section: Genetic Parametersmentioning
confidence: 95%